Historical reading of psychology - پڕۆفسیۆرى یاریدەدەر دکخۆر وٍومود ئیتراَیه حٍسٍن; واوۆسخاى یاریدەدەر سازان جوَر حىٍ غریب (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Understanding psychology and psychological aspects is an important step in the analysis and interpretation of hidden objects inside human that are influencing human behavior and are expressed through multiple methods and actions. This research deals with a precise study of the history of evolution and how psychology become independent and how it is combined with literature on the other. For the purpose of a deeper understanding of psychology, graphic drawings were created and at the same time, the development of psychology was explained through historical and epochal stages. Moreover, the study addresses the most important curricula and schools of psychology and highlights the most important approach of psychology which linked psychology to literature and linked applied sciences with human sciences.